Foyle's war. Set 1 [videorecording (DVD)] - Horowitz, Anthony, 1955- (2009)
Michael Kitchen stars as Detective Chief Inspector Christopher Foyle in this original PBS Masterpiece Theatre mystery series. Set in the beautiful southern English countryside amid the disorder and danger of World War II, Foyle's War takes place far from the glory of the front. His is an ordinary struggle, against everyday evil, in extraordinarily dangerous times.